Administrative mediation (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This paper aims to show what the current situation of administrative mediation, understanding in this expression both what can be done in headquarters administrative record as intrajudicial mediation when the conflict is judicialized. Sign that the former is unprecedented. And regarding the second is found that the CGPJ has designed mediation through private mediators completely ineffective in this jurisdiction. We intend to demonstrate that mediation should be channeled enhancing intrajudicial court settlement Article 77 LJCA and outline very briefly the way it should be implemented mediation headquarters administrative record by creating mediation administrative bodies.
Keywords: Mediation; transaction; mediation administrative bodies; private mediators.